The Exported Protein PbCP1 Localises to Cleft-Like Structures in the Rodent Malaria Parasite Plasmodium berghei - Haase, Silvia; Hanssen, Eric; Matthews, Kathryn; Kalanon, Ming; de Koning-Ward, Tania F. (PLOS ONE, 2013)
Protein export into the host red blood cell is one of the key processes in the pathobiology of the malaria parasite Plasmodiumtrl falciparum, which extensively remodels the red blood cell to ensure its virulence and survival. In this study, we aimed to shed further light on the protein export mechanisms in the rodent malaria parasite P. berghei and provide further proof of the conserved nature of host cell remodeling in Plasmodium spp. Based on the presence of an export motif (R/KxLxE/Q/D) termed PEXEL (Plasmodium export element), we have generated transgenic P. berghei parasite lines expressing GFP chimera of putatively exported proteins and analysed one of the newly identified exported proteins in detail. This essential protein, termed PbCP1 (P. berghei Cleft-like Protein 1), harbours an atypical PEXEL motif (RxLxY) and is further characterised by two predicted transmembrane domains (2TMD) in the C-terminal end of the protein. We have functionally validated the unusual PEXEL motif in PbCP1 and analysed the role of the 2TMD region, which is required to recruit PbCP1 to discrete membranous structures in the red blood cell cytosol that have a convoluted, vesico-tubular morphology by electron microscopy. Importantly, this study reveals that rodent malaria species also induce modifications to their host red blood cell.